Antiblack Joy: Transmedial Sīyāh Bāzī and Global Public Spheres. Issue 1 (March 2022) - Vaziri, Parisa
Abstract : Maryam Khakipour's 2004 The Joymakers and its 2008 sequel Shadi form an exemplary site for examining the dissemination and translation of Persian blackface across time, space, and media. The transmediality of sīyāh bāzī reveals a universal familiarity with the practice of blackface comedy that disrupts commonplace assumptions about its geographical and historical itinerary.